Analysis of the Floodlight Lighting Effect on the Visual Quality of the Phinisi Tower Building Facade - Mahsun Wahid; Nurul Jamala (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2021)
Lighting is one of the important factors to recognize the environmental situation. Lighting is needed by humans, with good lighting we can visually recognize objects clearly. The suitability of lighting with recommended light standards and the arrangement of building facades in accordance with the distribution of lighting will have an impact on the visual quality of a building. Along with the development of technology and information, people's lifestyles are increasingly advanced and developing. Likewise, the function of artificial lighting, which used to only function as lighting at night, has now developed into an important part of the aesthetic forming factor of a building. So there is a need for a survey to see how big the difference in perception of the visual quality of lighting is by using floodlights on the Phinsi Tower. The survey method of data collection used quantitative and qualitative research methods. Mixed methods are divided into quantitative methods (research using questionnaires and SPSS data processing) and qualitative (respondent perception, interview and observation). Based on the results of surveys and tests conducted on 17 simulation models, different results were obtained in each test model. This explains that the use of floodlights greatly influences the visual quality of the Phinisi Tower facade. Of the 17 lighting simulation models that have been made, Model 17 has the highest average score of 5.08 and the lowest is Model 10 of 2.53 (a rating scale of 1 to 7).